Proposals to apply environmental protection laws under new criminal laws - Bahil Jadaan, Jyan; Abbas Hasan, Qayssar (International Journal of Psychosocial Rehabilitation, 2020)
Awareness of environmental degradation and waste of natural resources in the early 1970s has led, at the state level, to the European Community and international more and more precise and binding. If, in the European Union, the normative arsenal seems close to exhaustiveness, the question of its effectiveness remains intact. The search for an effective sanction of environmental rules is currently inspiring a double movement: on the part of the European authorities, a reflection on the adaptation of the traditional remedies for criminal sanction and civil liability to the particularism of risk and environmental damage; on the part of the magistrates, a desire to be involved in the implementation of this new branch of law and international cooperation. Two proposals for directives from the Parliament and the Council bear witness to these new concerns. One tends to criminalize breaches of obligations deriving from Community law that cause or are likely to cause substantial damage to the environment (proposal of 26/06/2001: OJEC No. C-180 E, followed by a Council Framework Decision of 27 January 2003). The other relates to the creation of an environmental liability regime for the prevention and repair of damage (proposal of 23/01/2002, COM 2002 0021 COD: JOCE of 25 June 2002). These texts echo two conventions adopted under the auspices of the Council of Europe, one devoted to the responsibility for damage resulting from activities dangerous to the environment (Lugano, 21 June 1993), the other to protection of the environment through criminal law (Strasbourg, 4 November 1998)